Voices from Africa - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
Information and Communication Technologies Series: Voices from Africa, no 9. By the UN Non-Governmental Liaison Service (NGLS) United Nations, Geneva, 2000. 119 pp. Free of charge